"Onde em nós a casa mora" : o direito ao território às comunidades tradicionais - Adão, Clara de Oliveira (2021)
This study aims to discuss the right to territory, from its conceptualization and its importance for the processes of subjectivation in the construction of identity and sense of belonging. This theme is a frequent topic in social movements in Latin America and is extremely relevant. The specific objectives are to discuss the concept of territory and its uses. The approach to the right to territory in the legal system, from a constitutional perspective, going through the constitutionalization of environmental law. The discussion about the forms of extinction of territories, such as deterritorialization, territorial exclusion and aestheticization. And the explanation of territorial conflicts faced by traditional communities, both in the face of the National System of Conservation Units, as well as environmental licensing. A bibliographic and documental review was carried out, using the hypothetical deductive method; and quantitative analysis of secondary data provided by the Ministry of Environment, Chico Mendes Institute for Biodiversity Conservation, and the United Nations, in partnership with the International Union for Conservation of Nature and the National Geographic Society. A decolonial epistemological proposal is presented, from the Global South, based on Edgardo Lander, Anibal Quijano, Alvaro de Azevedo Gonzaga, and Boaventura de Sousa Santos. The theoretical framework is interdisciplinary and privileges Latin American contributions. For the legal approach, the works of Menelick de Carvalho Netto, Caio Jesus Granduque José, Luigi Ferrajoli, Júlio José de Araújo Junior, and Giselda Scheneider were used. The result of the research points to the territorial exclusion of traditional populations. It also points to the need to use an intercultural interpretation of the right to property to guarantee the right to territory. In addition, it is urgent to give to this right the respective legal protection, which needs to be addressed as a fundamental right, linked to the notion of human dignity, through a dual system of guarantees.